Nature-based experience in Venetian lagoon: Effects on craving and wellbeing in addict residential inpatients - Benvegnù, Giulia; Semenzato, Mauro; Urbani, Alberto; Zanlorenzi, Isadora; Cibin, Mauro; Chiamulera, Cristiano (Frontiers in Psychology, 2024)
It is known that exposure to the natural environment may positively modulate mental processes and behaviors; in particular, it can reduce stress, anxiety, and depressive symptoms. This suggests a potential integration of 'nature experience' into the treatment for substance use disorder (SUD), since various types of addiction are associated with anxiety and depression. Considering that only one study has been reported so far in patients with alcohol use disorder, the effect of nature experience in SUD patients needs to be further investigated. The aim of this study was to test the effects of the exposure to a natural lagoon environment on craving and measures of well-being in SUD patients, in comparison to the exposure to an urban environment. Methods: Twenty-four SUD patients were divided into three groups of 8 participants and exposed to two walking sessions (interspersed with a 1-week wash-out period) in a natural environment typical of the Venetian lagoon, an urban walk, or staying at the residential centre based on a Latin-square design. Before and after each session, drug craving, mood, well-being, agency, openness to the future, and restorativeness were assessed. Results: The Nature walk significantly decreased craving in participants compared to pre-walk values, and compared to craving after Urban walk, with the latter significantly increased vs. pre-walk values. The Nature walk significantly decreased negative mood and increased well-being and agency. Openness to the Future and Restorativeness measures showed significant improvement after Nature walk vs. Urban walk. On the other hand, craving scores after Urban walk positively correlated to negative mood and Sense of Negative Agency values, and negatively correlated to well-being scores. Discussion: Our results confirm that 'nature-experience' may improve mood, well-being, attention, stress-relief, openness, and sense of being active in SUD patients. Moreover, we also showed a specific effect on drug craving, a key symptom of SUD.